Ethnic minority science students in New Zealand : attitudes and learning environments - Lillis, David A. (Curtin University, 1999)
This thesis describes a study of the attitudes towards science and learning environments among junior secondary school science students in New Zealand, focussing particularly on Maori and Pacific Island students. The rationale for the research was that ethnic minority group students often experience difficulties in adapting to modern science education. The study was restricted to forms three, four and five of the New Zealand education system in order to focus attention primarily on the development of recommendations for enhancement of science education outcomes which relate to the early years of science education.The study aimed to investigate student attitudes towards science and their perceptions of their learning environments by using questionnaire surveys and interviews in order to produce complementary information about students' attitudes and perceptions. The study produced some unexpected findings. For example, Maori and Pacific Island students displayed more positive attitudes towards science than others, and female students displayed more positive attitudes than males. These findings contradict those of many previous studies.The findings of the study are used to provide input to the development of recommendations for the enhancement of educational outcomes for all students, but especially for ethnic minority students in science.